PENINGKATAN HASIL BELAJAR MATEMATIKA DENGAN MENGGUNAKAN PENDEKATAN KETERAMPILAN PROSES SEKOLAH DASAR NEGERI 32 - Gustiawan, Gustiawan; Margiati, K. Y.; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study is to describe the Improvement of Student Learning Outcomes in Mathematics Learning Using Process Skill Approach in Class IV of SD Negeri 32 Pontianak Tenggara. The method used is descriptive method, with the form of classroom action research, and collaborative. There is an increase of learning outcomes with the process skill approach in each cycle is always increased from the first cycle (first meeting) is 50%, in cycle I (second meeting) is 52.294% there is an increase in learning outcomes with a process skill approach in each cycle always increased starting from cycle II (first meeting) that is 94,12%, and in cycle II (second meeting) become 91,18%. Thus it can be said that the learning achievement in cycle II has met the target. Can be concluded by using the process skill approach, the achievement of learning mathematics of grade IV students of State Elementary School 32 Pontianak Southeast in material counting the range and area of jajargenjang and triangle have increased.Keywords :Study Result, Math, Skill Processing Approach